Is It All About Attitude? Owner–Manager Attitude to Digitalisation, Digitalisation Level, and SME Competitive Performance - Joensuu-Salo, Sanna; Rajala, Anni; Laine-Kronberg, Annika (Nanyang Technological University, 2025)
This study explores how digitalisation and digital technologies impact SME business models and competitiveness. It examines the relationship between SME owner–manager attitudes towards digitalisation, the level of digitalisation, and competitive performance. Drawing on Upper Echelons Theory (UET) and SME digitalisation literature, the study employs a quantitative survey of 269 Finnish SME managers, analysed through structural equation modelling. A positive owner–manager attitude towards digitalisation enhances SME digitalisation levels. This attitude indirectly impacts competitive performance, mediated by the firm’s digitalisation level. The findings demonstrate the influence of individual cognitive processes on firm-level digitalisation and performance, highlighting the significant role of owner–manager attitudes in SME digitalisation and competitive advantage. Furthermore, the results emphasise a micro-foundations perspective on the antecedents of digitalisation in SMEs.
Keywords: digitalisation; competitive performance; attitude; SME; upper Echelons theory; fi=Strateginen johtaminen|en=Strategic Management|